The Effectiveness of AI-Powered Advertising on Startup Growth Compared to Traditional Methods A Comparative Study Between Traditional and AI-Powered Advertising Methods (Comprehensive Journal of Science, 2026)
This research aims to examine the effectiveness of AI-powered advertising on startups by comparing traditional advertising with advertising supported by artificial intelligence. The analytical and comparative approaches were employed to highlight the fundamental differences in the efficiency and effectiveness of modern advertising methods compared to traditional ones. The results showed that advertising, especially through AI technologies, significantly contributes to enhancing customer engagement, increasing reach, and thereby supporting the growth of startups. The researcher recommends that entrepreneurs adopt innovative advertising methods to achieve a sustainable competitive advantage.
Keywords: startups, artificial intelligence, traditional advertising, marketing performance, financial performance